Enhancing Literary Appreciation Through Badi’ Teaching Materials Based on Adabiyah Syawahid for Arabic Literature Students in Indonesia and Brunei Darussalam (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
To balance and improve Arabic language education in Indonesia, ensuring that it competes on a global and international level, one crucial component that needs immediate enhancement is the quality of teaching materials, which must be aligned with an up-todate curriculum. The urgency of this research is to provide solutions for suboptimal learning caused by inadequate teaching materials. Thus, the researchers have developed Badi’ teaching materials based on Adabiyah Syawahid to increase the literary appreciation of Arabic literature students in Indonesia and Brunei Darussalam. This initiative is a preliminary test before further research in Arab countries. The objectives of this study are: 1) To detail the creation and characteristics of Badi’ teaching materials based on Adabiyah Syawahid and evaluate their feasibility in Badi’ education to enhance literary appreciation; 2) To measure the effectiveness of these teaching materials in improving literary appreciation. The researchers employed a simplified R&D design method based on the Borg and Gall model, comprising six steps: needs analysis, development planning, product drafting, product revision, field testing, and module refinement. Data collection methods included observation, interviews, questionnaires, and tests, with quantitative data analysis using the Likert and t-test methods. The results of this research indicate significant differences between pre-test and post-test scores of students using the developed Badi’ modules, as shown by the t-test value (8.422) being greater than the t-table value (2.101) and a significance value (0.000) less than alpha (0.050), indicating that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.